2018
DOI: 10.9744/ijbs.1.2.70-79
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Brand Awareness and Country of Origin on Purchase Intention with Mediation of Self Congruity on Chinese Brand Automotive Products Wuling

Abstract: This study aims to analyze the relationship of Brand Awareness and Country of Origin by using Self Congruity as mediation for Purchase Intention. This causal study used a questionnaire-based survey as a data collection method, and 200 questionnaires have been distributed to sample respondents of this study. The selection of this research sample used a purposive sampling technique with criteria determined by the researcher. Data analysis used the Partial Least Square (PLS) technique. The results showed that fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
9
0
5
Order By: Relevance
“…Research conducted [20], [21] revealed that social media is very helpful for marketing in encouraging consumer purchase intentions. The same thing was also expressed by [22], [23] which emphasized that in addition to social media, purchase intention was also influenced by the brand and country of origin of the brand. This shows that brand reputation and the strength of social media greatly affect consumers' intention to make a purchase.…”
Section: Buying Intentionmentioning
confidence: 69%
“…Research conducted [20], [21] revealed that social media is very helpful for marketing in encouraging consumer purchase intentions. The same thing was also expressed by [22], [23] which emphasized that in addition to social media, purchase intention was also influenced by the brand and country of origin of the brand. This shows that brand reputation and the strength of social media greatly affect consumers' intention to make a purchase.…”
Section: Buying Intentionmentioning
confidence: 69%
“…In Indonesia, most of the MNCs are considered commercial organizations, where marketing is usually the dominant function, and public relations is treated as another element of the marketing mix in MNCs. Even though they are part of marketing, their programs are entirely different from marketing because, in the marketing department, the marketing practitioners try to improve or increase the product sales, but for marketing public relations practitioners, the most important things is not only improving the image of the product but also maintaining the brand awareness of the product in the customer mind until it reaches the top of mind in brand awareness level, because the higher level of conformity of self-image prospective buyers with the product, the higher purchase intention is felt ( Setiadi E, Adiwijaya M and Subagio H, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Brand awareness refers to the degree of a brand's ability to establish strong appeal and presence in a customer's mind (Foroudi et al, 2018;Setiadi et al, 2018). A customer with higher brand awareness is more inclined to remember or distinguish the brand and associate it with its attributes (Anand, 2018;Wijaya et al, 2020).…”
Section: The Moderating Role O F Brand Aw Arenessmentioning
confidence: 99%
“…According to Kumar & Arthi (2020), brand awareness serves as an essential gateway to the customer decision-making process because, without brand awareness, a customer does not understand or conscious that he or she has an option about this particular brand. Thus, the degree of brand awareness can strengthen brand positioning in the customer's consideration set and accordingly affect customer brand selection and decision-making (Phung et al, 2019;Wijaya et al, 2020;Setiadi et al, 2018). As discussed by Lee et al (2019) earlier, product innovation serves as a brand's manifestation of genuine concerns of its customer welfare, as they produce new, improved products to meet customer needs.…”
Section: The Moderating Role O F Brand Aw Arenessmentioning
confidence: 99%
See 1 more Smart Citation